The Impact of Islamic Corporate Governance, Islamic Intellectual Capital and Islamic Financial Performance on Sustainable Business Islamic Banks - Siswanti, Indra; Salim, Ubud; Sukoharsono, Eko Ganis; Aisjah, Siti (International Journal of Economics and Financial Issues, 2017)
The objective of the study is to analyze the impact of Islamic corporate governance, Islamic intellectual capital and Islamic financial performance on sustainable business in Islamic banks. This research uses quantitative approach with secondary data, period 2010-2015. Sample use sensus method with the number of samples are 9 (nine) Islamic banks. Analysis of data testing use partial least square (PLS) supported by in-depth interview. The results showed: 1). Islamic corporate governance has a significant impact on Islamic financial performance. 2). Islamic intellectual capital has a significant impact on Islamic financial performance. 3) Islamic corporate governance has no significant impact on sustainable business. 4). Islamic intellectual capital has a significant impact on sustainable business. 5) Islamic financial performance has a significant impact on sustainable business. 6). Islamic financial performance full mediate the impact of Islamic corporate governance on sustainable business. 7). Islamic financial performance partial mediate the impact of Islamic intellectual capital on sustainable business. Keywords: Islamic corporate governance, Islamic intellectual capital, Islamic financial performance, sustainable business JEL Classifications: G3, G30